Desenvolvimento de vitrocerâmicas com estrutura NASICON condutoras por íon sódio da família NaGe2(PO4)3 - Ortiz Mosquera, Jairo Felipe (2015)
Sodium batteries have a promising future owing to the low cost and abundance of sodium in nature. This growing interest has led to the quest for materials to optimize and improve the operation of these devices. Among the components of batteries, electrolyte plays a fundamental role in terms of current density and battery life. In this context, materials with NASICON structures are promising candidates for solid electrolytes because their crystalline structure with open channels promotes high ionic conductivity. Synthesizing NASICON materials by the glass-ceramic route offers several advantages such as easy manufacturing into desired shapes or sizes, low porosity and good microstructural control. Considering the abovementioned factors, the objective of this work was to synthesize and characterize glass-ceramics of the Na1+xAlxGe2-x(PO4)3 and Na1+yGe2SiyP3-yO12 systems for application as solid electrolytes in sodium-ion batteries. The results indicated that the addition of aluminum and silicon improved the glass-forming ability of NAGP and NGSP precursor glasses. Moreover, a thermal analysis revealed the tendency for NAGP precursor glasses to nucleate homogeneously. All the glass-ceramics heat-treated at the crystallization temperature of the precursor glasses (Tx), presented a NASICON structure. The electrical characterization of the glass-ceramics indicated that increasing the aluminum and silicon content enhanced the material’s ionic conductivity because it led to an increase in charge carrier density. To analyze the effect of heat treatment on the microstructure and ionic conductivity, the most conductive compositions of each system (x = 0.8 and y = 0.8) were also crystallized in heat treatments at 800 and 900°C to improve the ionic conductivity.